Scientific Literacy Linked to Attitudes Toward COVID-19 Vaccinations: A Pre-Registered Study - Motoki, Kosuke; Saito, Toshiki; Takano, Yuji (Frontiers in Communication, 2021)
The ongoing COVID-19 pandemic, which began in early 2020, is a global public health crisis. To prevent the spread of COVID-19, it is necessary to promote vaccine administration and preventive behaviors (e.g., mask, handwashing, social distancing). However, some people have negative attitudes toward vaccine administration and preventive behaviors. Based on the information-deficit model, the present study investigated how scientific literacy and perceived understanding of COVID-19 are associated with attitudes toward COVID-19 vaccinations and preventive behaviors. The findings demonstrated that both scientific literacy and perceived understanding of COVID-19 vaccines were positively associated with attitudes toward COVID-19 vaccines. Additionally, perceived understanding of COVID-19 preventive behaviors (but not scientific literacy) was positively associated with attitudes toward/practice of COVID-19 preventive behaviors. Collectively, our findings revealed the role of cognitive factors in preventing the global public health crisis and demonstrated the roles of objective and subjective knowledge on attitudes toward COVID-19 vaccinations and preventive behaviors.